Does institutional trading drive commodities prices away from their fundamentals: Evidence from a nonparametric causality-in-quantiles test - Babalos, Vassilios; Balcilar, Mehmet (Academic Press Inc Elsevier Science, 2017)
Motivated by the heated debate on commodities market financialization hypothesis we set off to examine the asymmetric relationship between commodities funds flows and commodities market prices by employing a novel nonparametric causality-in-quantiles. With respect to our results, while the linear Granger causality tests fail to provide evidence of causality in either direction the more robust causality-in-quantiles approach highlights partial evidence of one way causality running from market returns to commodities fund flows. Finally, substantial evidence of predictability of the variance of commodities market returns emanating from commodities fund flows is also reported. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Commodities markets; Commodities fund flows; Quantile causality; Volatility